PERAN PENDIDIKAN ISLAM DALAM MEMBENTUK MANUSIA INDONESIA YANG BERKARAKTER DAN BERKEPRIBADIAN - Efendi, Sofian (AZKIYA, 2018)
Various crisis that has swept our society, not only penetrated the economic field, but also character and personality of our nation. Degradation of confidence and identity as a nation that upholds its original character and personality polite and friendly now that occur almost reached its nadir. Also the moral decadence among students occurs as the impact. Though the character and personality are formed from a good education becomes one of the important preconditions that determines the quality of human resources. While efforts to improve the character and personality of the community have been made parties. One of these Islamic educational institutions. Of course, before fixing the character and personality of its people, the practitioners of Islamic education should equip themselves with character and a good personality as well, so that all his actions become community role model. The author offers abackrest formation of character and the perfect personality that is in the prophet SAW and then applied through Islamic Education.